Intermodaler Nutzerpreisvergleich auf Personenverkehrsverbindungen. - Hietzschold, Sven (DVV Media Group, 2008)
Wie unterscheiden sich die Nutzerpreise des Eisenbahn-Hochgeschwindigkeitsverkehrs, des Pkw-Verkehrs und des Flugverkehrs auf ausgewählten nationalen und internationalen europäischen Personenverkehrsrouten? Die Untersuchung gibt eine Übersicht über die Wettbewerbssituation der Verkehrsträger. Die Preisunterschiede zwischen den Verkehrsträgern fallen je nach betrachteter Relation sehr unterschiedlich aus.

This report deals with a comparison of user tariffs for travel by air, high speed trains and private cars on selected domestic and international routes in Europe (passenger transport), in order to offer an overview of the level of competition among the various modes of transport. The outcome is that there is a notable difference in fares offered by operators on the routes under review. Network carriers' air fares showed very significant variations whereas, by comparison, tariffs for rail journeys and trips by motor car had only minor differences. In those countries where road user charges are common-place, travel by rail turned out to be much more attractive than the use of private cars. Rail travel was notably cheaper in countries applying road user charges compared with countries where this was not the case. On average, low-cost airlines tended to offer the most attractive fares. Costs associated with access to the ÖPNV system - and for onward travel - did not make any notable impact on the total price. The fuel surcharge added to the price of an air ticket - based on the kerosene fuel tax set at the level of the mineral oil tax - has led to an increase of air fares by some seven per cent. This is not expected to affect the choice of a particular mode of transport.
Intermodal user tariff comparison of European routes (passenger transport).
Keywords: Verkehr; Verkehrsnachfrage; Wettbewerb; Personenfernverkehr; Eisenbahnverkehr; Luftverkehr; Personenkraftwagenverkehr; Preisvergleich; Verkehrsmarkt; Verkehrsträger; Verkehrsleistung; Verkehrsforschung; Verkehrsangebot; Hochgeschwindigkeitsverkehr; Modal Split